Research on Anti-Submarine Warfare Method of Unmanned Aerial Vehicle Cluster Based on Area Coverage and Distributed Optimization Control - Yongzhao Yan; Yi Liu; Ying Bi; Qian Wang; Huazhen Cao; Ziping Yu; Kangkang Li; Bo Wang; Xiaoping Ma (Drones)
Maritime security is vital to national security. The application of unmanned aerial vehicle (UAV) clusters in marine anti-submarine warfare (ASW) presents a new and significant challenge worthy of in-depth study. Based on the anti-submarine principle of geomagnetic anomaly detection and the Find-Fix-Track-Target-Engage-Assess (F2T2EA) framework, this paper divides UAV cluster ASW operations into two stages: regional coverage and cooperative convergence. The regional coverage stage enables the UAV cluster to perform a broad search for submarines, while the cooperative convergence stage facilitates the precise positioning of detected submarines. In simulation, the combat scenario of five UAV clusters against a submarine is carried out. In the given area, the UAV can locate and stalk the target submarine in limited time. Simulation results demonstrate the feasibility of the proposed approach, providing reference for advancing marine ASW capabilities and related research.